A literature review about acculturation on the American Anthropologist : reduced version - Castro, Joaquim Filipe (2020)
The research accomplished a literature review about acculturation on the earlier American Anthropologist journal. Acculturation research appeared on the North American Anthropology; later came to Sociology and Psychology. The main models to approach acculturation followed the historical evolution of the North American culture, and the earlier research barely considered the main dimensions of the acculturation concept. Assimilation and, in a lesser degree, fusion were the preferred models during colonial and imperial times, and American Indigenous were the main researched cultural group. Acculturation was approached as type of cultural influences, and Indigenous cultural change was the main concern. Yet, interaction and learning were not the main concerns. The multicultural model appeared already in the earlier literature, yet it was related to fusion.